PERAN DAN POSISI INFORMASI TEKNOLOGI (IT) DALAM DAKWAH DAN KOMUNIKASI - Ariani, Anita (Alhadharah: Jurnal Ilmu Dakwah, 2014)
This paper discusses the role of dakwah with multimedia through information and communication technologies in terms of urgency, the theological foundation and theoretical foundation. Da'wah can be done anytime and anywhere through a variety of media with the use of information and communication technology. The competence of communication means ability to communicate well, efficiently and effectively with anyone, any level locally, nationally and globally, as well as the control of IT for the benefit of the effectiveness of communication such as fax, email, etc. While personal competence in a broad sense is a high work ethic, hard work, discipline, honesty, simple and not wasteful